Financial performance comparison for ABC Farm - Newkirk, Kevin J. (Kansas State University, 2015)
This thesis had two objectives. One objective was to compare one northeast Kansas farm's financial performance from 2002 through 2011 to various groups of farms participating in the Kansas Farm Management Association (KFMA) during the same period. The second objective was to compare the crop acreage growth trends of the same northeast Kansas farm from 2002 through 2011 to the same groups of farms participating in the KFMA. In this thesis the northeast Kansas farm was referred to as ABC Farm. The purpose of this thesis was to provide ABC Farm's owners and management with information that could be used to formulate long-term goals for ABC Farm and to help identify strategies for achieving those goals. ABC Farm's 10-year financial performance was compared to six different KFMA member groups using 12 different financial measures or ratios. The KFMA groups included all NE region farms, NE region farms in the highest value of farm production (VFP) category, STATE irrigated crop farms, NE region farms in the highest net farm income quartile, NE region farms in the highest crop acreage category, and NE region farms in the lowest adjusted total expense ratio quartile. The 12 financial measures or ratios included VFP, net farm income, adjusted total expense ratio, operating profit margin ratio, asset turnover ratio, percent return on assets, VFP per worker, total crop acres farmed, crop machinery investment per crop acre, crop machinery cost per crop acre, current ratio, and debt to asset ratio. ABC Farm's 10-year average financial performance was better than the 10-year average of any KFMA group for most financial measures. ABC Farm's VFP, net farm income, operating profit margin ratio, VFP per worker, total crop acres, and current ratio were all higher than any KFMA group. ABC Farm's adjusted total expense ratio, crop machinery cost per crop acre, and debt to asset ratio were also lower than those of the various KFMA groups compared to. ABC Farm did not compare favorably to other KFMA groups for some of the financial measures. ABC Farm's average crop machinery investment per crop acre was higher than every group. ABC Farm's average asset turnover ratio was lower than every group. ABC Farm's average return on assets was lower than all but one group, all NE region farms.
Keywords: Financial ratios; Benchmarking; Economics, Agricultural (0503); Management (0454)